(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2020)
Co-precipitaion method and sol-gel technique were used to prepare semiconductor microcrystalline and nanosized SnO2/Sb2O5 and Со/SnO2/Sb2O5 (0.15 wt.% Sb) materials aimed to create high sensitive hydrogen sensors. Morphology and phase composition of the obtained samples were studied by SEM, TEM and XRD methods. It was found that microcrystalline SnO2/Sb2O5 material with particle size of 1–30 µm was obtained by a co-precipitation method and nanosized SnO2/Sb2O5 material with particle size of 5–25 µm (an average size – 12 nm) was obtained by a zol-gel method. Only cassiterite phase was detected for both microcrystalline and nanosized materials. Sensitivity measurements of the sensors were carried out with using of air-hydrogen mixtures in the concentration range of 40 – 1145 ppm Н2, and dynamic characteristics (response time and relax time) were evaluated for 40 ppm Н2 at different heater power consumptions – 0.25 and 0.35 W. To increase sensitivities of the sensors, cobalt oxide, a known catalyst for hydrogen oxidation, was added to the resulting SnO2/Sb2O5 materials. It was shown that the sensors obtained by a zol-gel method demonstrate more significant sensitivity to hydrogen concentration in comparison with the sensors obtained by a co-precipitation method. It is probably associated with a higher surface area of the nanomaterial that agrees with its smaller particles as compared with the particles of the microcrystalline material. The Co-containing sensors based on the nanosized SnO2/Sb2O5 material are established to reveal higher sensitivity to Н2 than microcrystalline Co/SnO2/Sb2O5 sensors. The Co-containing sensors based on the nanosized SnO2/Sb2O5 material were found to have better dynamic characteristics than microcrystalline Co/SnO2/Sb2O5 sensors. The sensitivities increase and the response and recovery time decrease were found for both sensor materials at increasing of the sensors heater power consumption. The obtained results can be explained with different degree of energy surface heterogeneity of the used materials. The sensor response time is determined by the time of dynamic equilibrium establishment of the hydrogen oxidation reaction on the sensor surface and the recovery time is determined by the time of desorption of the H2 oxidation reaction products (H2O) from the sensor surface. Because of the processes, the sensor with a gas sensitive layer based on the nanosized material possessing with more homogeneous structure of its surface (according to the obtained TEM data) demonstrates improved gas sensitive properties in comparison with the sensor based on the microcrystalline material. The obtained results concerning the sensitivities to H2 and the dynamic parameters of the created sensors point to possibility of effective usage of the sensors based on the nanomaterial to detect H2 in air in the practice.